Changes in hillslope hydrology in a perched, shallow soil system due to clearcutting and residual biomass removal. Issue 26 (2nd November 2020) - McCarter, Colin P. R.; Sebestyen, Stephen D.; Eggert, Susan L.; Kolka, Randall K.; Mitchell, Carl P. J.
Abstract: Sustainable fuels legislation and volatility in energy prices have put additional pressures on the forestry sector to intensify the harvesting of biomass for "advanced biofuel" production. To better understand how residual biomass removal after harvest affects forest hydrology in relatively low slope terrain, a Before‐After‐Control‐Impact (BACI) study was conducted in the USDA Forest Service's Marcell Experimental Forest, Minnesota, USA. Hydrological measurements were made from 2010–2013 on a forested hillslope that was divided into three treatment blocks, where one block was harvested and residual biomass removed (Biomass Removed), the second was harvested and residual biomass left (Biomass Left), and the last block was left as an Unharvested Control. The pre‐harvest period (2 years) was 2010–11 and post‐harvest (2 years) was 2012–13. Water table elevation at the upslope and downslope position, subsurface runoff, and soil moisture were measured between May–November. Mixed effect statistical models were used to compare both the before‐after and "control" treatment ratios (ratios between harvested hillslopes and the Unharvested Control hillslope). Subsurface runoff significantly increased ( p  < .05) at both harvested hillslopes but to a greater degree on the Biomass Left hillslope. Greater subsurface runoff volumes at both harvested hillslopes were driven by substantial increases during fall, with additional significant increases during summer on the Biomass Left hillslope. The hydrological connectivity, inferred from event runoff ratios, increased due to harvesting at both hillslopes but only significantly on the Biomass Left hillslope. The winter harvest minimized soil disturbance, resulting in no change to the effective hydraulic conductivity distribution with depth. Thus, the observed hydrological changes were driven by increased effective precipitation and decreased evapotranspiration, increasing the duration that both harvested hillslopes were hydrologically active. The harvesting of residual biomass appears to lessen hydrological connectivity relative to leaving residual biomass on the hillslope, potentially decreasing downstream hydrological impacts of similar forestry operations. Abstract : In a hillslope‐scale field experiment, removal of residual biomass after forest harvesting results in less significant changes to runoff generation than does leaving residual biomass behind.